Breastfeeding a Premature Baby During the Covid-19 Pandemic in Perinatology: An Exploration of Mothers' Experiences - Syafrida Hanum; Yeni Rustina; Fajar Tri Waluyanti (SAGE Publishing, 2023)
This study was conducted to explore the meaning of mothers' experiences of breastfeeding premature babies while being treated in the perinatology room during the COVID-19 pandemic. A descriptive phenomenological design was used in this study to describe the meaning of mothers' experiences. In-depth interviews were conducted with 11 mothers. The analysis of transcribed data resulted in three themes: (1) The pandemic has made it difficult for me to meet my baby, (2) Breastfeeding is not easy, and (3) I am a breast milk pumper. The breastfeeding experience of having a premature baby and being cared for by perinatology during a pandemic is full of challenges and limited support. The results of this study suggest that a review of the current regulations be carried out, and the staff be given continuing lactation education to strengthen breastfeeding support to mothers with premature babies.